Russian Economic Report, No. 26, September 2011 : Growing Risks - World Bank (World Bank, Washington, DC, 2017)
Russia's economic growth slowed in the second quarter of 2011 as the inventory restocking cycle waned. High oil prices have kept the external current account in surplus but capital outflows continue. Gradually improving labor market conditions and access to credit and external borrowing are supporting domestic consumption but consumer confidence and external risks are constraining a more robust growth in domestic demand. Inflation is on a downward trend because of seasonal factors. The short-term fiscal situation is favorable mainly because of high oil prices with an almost balanced budget this year. But a large non-oil deficit requires concerted medium-term fiscal adjustment to replenish fiscal buffers and to move toward long-term sustainable levels of the non-oil deficit.